2021
DOI: 10.2147/cia.s303246
|View full text |Cite
|
Sign up to set email alerts
|

Association Between High-Sensitivity Troponin T on Admission and Organ Dysfunction During Hospitalization in Patients Aged 80 Years and Older with Hip Fracture: A Single-Centered Prospective Cohort Study

Abstract: Background Prognostic evaluation of elderly patients with hip fracture is an issue that has been highly concerned by clinicians. Only a few studies have focused on organ dysfunction after hip fracture in the elderly. This study aimed to investigate the association between high-sensitivity troponin T (hs-TnT) at admission and organ dysfunction during hospitalization in elderly patients with hip fracture. Methods We enrolled 168 patients with hip fracture who were aged 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Acute organ dysfunction in older patients is often a continuation and exacerbation on the basis of chronic degeneration or injury [ 10 ]. In this study, the HFHFS group had more chronic heart disease preoperatively, while the significant association between HFHFS and postoperative cardiac dysfunction was also confirmed by subsequent multivariate regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute organ dysfunction in older patients is often a continuation and exacerbation on the basis of chronic degeneration or injury [ 10 ]. In this study, the HFHFS group had more chronic heart disease preoperatively, while the significant association between HFHFS and postoperative cardiac dysfunction was also confirmed by subsequent multivariate regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative organ dysfunction referred to the changes that occurred after fracture surgery or worsened on the basis of preoperative dysfunction. Diagnostic criteria for postoperative cardiac, brain and renal dysfunction were based on Diagnostic Criteria for Multiple Organ Dysfunction Syndrome in the Elderly (MODSE) (draft, 2003) [ 10 ] ( Table 1 ). Meanwhile, the Confusion Assessment Method for Intensive Care Unit (CAM-ICU) was applied for the diagnosis of delirium during hospitalization [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…N. van der Linden et al ( van der Linden et al, 2016 ) reported that the maximum fluctuations in cardiospecific TnT concentration in a patient with CKD during the 24-h investigation period were about 50 ng/L, while the fluctuations in cardiospecific TnT levels during 1 h were about 20 ng/L, which, by the way, is a very significant contribution to the laboratory diagnosis of MI. So, for example, if we take into account modern algorithms for diagnostics of non-ST-segment elevation MI ( Table 1 ) ( Qin et al, 2021 ) (where the change in the levels of cardiospecific Tns within 1–2 h by only 5–10 ng/L is diagnostically significant), we can say that cardiospecific TnT circadian rhythms may affect the diagnostics of AMI and contribute to overdiagnosis ( van der Linden et al, 2016 ). Cardiospecific TnI levels showed slightly higher fluctuations in concentration during the day compared to the study by L. Klinkenberg et al ( Klinkenberg et al, 2016b ), however, they would not reach the thresholds of 5–10 ng/L and thus would not have a significant effect on one- and 2-h algorithms of MI diagnostics.…”
Section: Circadian Rhythms Of Cardiospecific Tns: Possible Mechanisms...mentioning
confidence: 99%
“…Besides, along with the necrosis of cardiomyocytes (CMC), there are other mechanisms of cardiospecific Tns release from CMC and/or the increase of cardiospecific Tns concentration in blood serum. Thus, several clinical studies give evidence of very frequent increase in cardiospecific Tns concentration in various pathologies ( Lindner et al, 2014 ; Saad et al, 2015 ; Wu et al, 2018 ; Askin et al, 2020 ; Qin et al, 2021 ). At the same time, the mechanism of troponin increase in these diseases is not associated with the ischemic necrosis of CMC—the main mechanism of cardiospecific Tn levels increase in MI.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, along with the necrosis of cardiomyocytes, there are other mechanisms of cardiac troponin release from myocardial cells and/or the increase in cardiac troponin concentration in blood serum. Thus, several clinical studies give evidence of very frequent increase in cardiac troponin concentration in various pathologies [ 24 28 ]. At the same time, the mechanism of troponin increase in these diseases is not associated with the ischemic necrosis of myocardial cells—the main mechanism of troponin levels increase in myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%